EPEN-07. PATTERNS OF EXTRANEURAL METASTASES IN PEDIATRIC SUPRATENTORIAL EPENDYMOMA: CASE SERIES AND REVIEW OF THE LITERATURE. (4th December 2020) - Chan, Priya P; Whipple, Nicholas S; Perry, Arie; Solomon, David A; Zhou, Holly; Linscott, Luke L; Kestle, John R W; Bruggers, Carol
Abstract: BACKGROUND: Ependymomas account for 10% of all malignant pediatric intracranial tumors. Standard therapy includes maximal safe surgical resection followed by involved-field radiation. Up to 50% of localized pediatric ependymomas recur. Extraneural metastases at time of recurrence are rarely reported. OBJECTIVE: To describe extraneural metastases of pediatric ependymomas. METHODS: Retrospective review of patients' medical records and literature review. RESULTS: Three patients with history of locally recurrent, supratentorial ependymoma developed extraneural metastases: one in a cervical lymph node, one with a scalp nodule, and one with a dural lesion. Each extraneural recurrence had similar histologic and molecular features as the initial diagnosis. The cervical lymph node recurrence was treated with multimodal therapy; she is without disease four years later. The isolated scalp nodule occurred at the exit site of a subgaleal drain placed during prior resection. Following nodule resection, he developed additional scalp and lymph node disease and is receiving palliative care. The isolated dural recurrence occurred at the exit site of a ventriculoperitoneal shunt placed following a previous resection. She died of progressive disease 18 months after dural lesion resection. Reports of lymph node, scalp, and dural metastases of ependymomas are exceedingly rare, and outcomes are poor. CONCLUSIONS: Extraneural manifestations of ependymoma are rare. Regional seeding from prior surgical procedures may play a role in metastatic spread. Extraneural metastases should be considered in children previously treated for ependymoma who develop local findings even in the absence of CNS relapse. Salvage therapy with curative intent should be considered using a multimodal approach.